Effect of inactive Rabies virus vaccine on hematological Parameters in species Roussettus aegyptiotiacus (Latakia University Journal -Biological Sciences Series, 2020)
The research aimed to study the immune response of species Roussettus aegyptiacus (family Pteropodidae) against Rabies virus. We used adult animals randomly: inactive virus with a main dose and two supportive doses in the third and tenth days, after that we compared the total number of red and white blood cells. We studied the formula of white blood cells and the total protein concentration before and during the experiment. The result showsd:• Significant increase in red blood cell (RBC) counts.• Significant increase in leukocytes and lymphocytes proportion in tenth day and significant decrease in fourteenth day.• Significant decrease in Neutrophils and Monocytes percentage ratios after doses compared with control.• No significant differences between basophiles and eosinophile percentage ratios after the doses.• Increased of total protein concentration after doses in the day ten of the experiment compared with control.